Developing interactive materials of writing non-literary texts based on flipbooks for secondary school students - Yuni Hajar; Elly Prihasti Wuriyani; Muhammad Joharis Lubis (UNIB Press, 2023)
This study aims to produce and determine the effectiveness of interactive material for writing non-literary texts based on flipbooks for class X students of MAN 2 Langkat. This research is a Research and Development (RnD) research using the ADDIE development model. There are three subjects in this development research. The first, validators consist of two material experts and two design experts. The four validators are Postgraduate Lecturers at Medan State University. Second, two teachers of Indonesian subjects. And the last are the students of class X MAN 2 Langkat totalled 96 people from three different classes, namely X MIA, X IIS, and X IIA. The data collection instruments used were in the form of a teacher needs analysis questionnaire, a student needs analysis questionnaire, a material and media expert validation sheet, a teacher validation sheet, and a student response sheet. Individual trials obtained